Susanna Wesley, mother of John and Charles - Ludwig, Charles, 1918-; Bowers, Tim (Milford, Mich. : Mott Media, 1984)
A biography of the woman who married the well-known preacher, Samuel Wesley, and was the mother of John, founder of Methodism, and Charles, famous for the more than 6,000 hymns he wrote during his lifetime.
Includes index.
Bibliography: p. [187]-188.
Keywords: Wesley, Susanna, -- 1669-1742 -- Juvenile literature; Wesley, Susanna, -- 1669-1742.; Methodists -- England -- Biography -- Juvenile literature; Methodists